Kajian Nilai Pendidikan Islam dalam Teks Tembang Macapat: Studi Nilai Pendidikan Islam Berbasis Budaya - Mulyono, Mulyono (UIN Maulana Malik Ibrahim Malang, 2007)
This research examines the contents of Islamic Education values in the texts of Tembang Macapat. Since the alim ulama, Wali Songo, Juru Dakwah, Kiai, ustaz, the educators, the men of letters, even the intellectuals, and also the experts of Javanese culture, especially since the middle era (The Demak Kingdom Era) until now often put many religious lessons and life in general as well as special education written and conveyed through